VizieR Online Data Catalog: Pismis 18 photometry and radial velocities (Hatzidimitriou+, 2019) - Hatzidimitriou, D.; Held, E. V.; Tognelli, E.; Bragaglia, A.; Magrini, L.; Bravi, L.; Gazeas, K.; Dapergolas, A.; Drazdauskas, A.; Delgado-Mena, E.; Friel, E. D.; Minkevi?Ci-Ut?E, R.; et al. (2019)
The data for Pismis 18 were obtained in May and June 2014 with FLAMES on the VLT-UT2 telescope at the European Southern Observatory. (1 data file).
Keywords: Clusters: open; Photometry; Radial velocities